GROUNDING CONNECTOR - BOLING, Dale; BENDLAK, Thomas; HOLDER, Gregory, Dean; WILMOTH, Brent; BARCEY, Christian (2025)
A grounding connector can include a connector body and a shear bolt. The connector body can have a recess sized to receive one or more conductors and a threaded portion. The shear bolt can be sized to engage the threaded portion of the connector body to secure the one or more conductors within the recess. When the shear bolt is tightened into the threaded portion of the connector body, the shear bolt can retain the one or more conductors within the recess. When the shear bolt is subject to a shear torque, a head of the shear bolt can shear from a body of the shear bolt. The shear torque can correspond to a target compression force applied between the shear bolt and the one or more conductors.